Identification of risk factors associated with hyponatremia in psychiatric patients: a case-control study - Powle, Himani; Shet, Ashvitha; Mendonca, Arline; Thulasi, Lakshmi; Poojari, Pooja; Thunga, Girish; Munoli, Ravindra; Kunhikatta, Vijayanarayana (Medicine and Pharmacy Reports, 2022)
Background and aims. Prompt recognition and optimal management of hyponatremia helps the physician devise a better treatment plan to prevent future complications in patients. Hence this study aims to identify the risk factors associated with hyponatremia in psychiatric patients. Methods. A case-control study was conducted among psychiatric inpatients in a tertiary care teaching hospital. Patients admitted from January 2013 to December 2017 were identified using ICD-10 code F01-F99. Patients with serum sodium levels < 135 mmol/L were considered to have hyponatremia and between 135-145 mmol/L as controls. Factors associated with hyponatremia were identified by multiple logistic regression, and the odds ratio (OR) was calculated. Results. Based on the inclusion and exclusion criteria, 264 cases of hyponatremia and 253 matching controls were included in the study. The mean age of patients with hyponatremia was 56.4 ± 16.8 years compared to 39.6 ± 13.9 years in controls, and 65.7% of them were males. Seizure disorder (OR = 3.14, p = 0.047), bipolar disorder (OR = 6.03, p = 0.001), depression (OR = 4.78, p = 0.0005), use of quetiapine (OR = 2.11, p = 0.007) and insulin (OR = 3.53, p = 0.038) were independent risk factors associated with development of hyponatremia. Conclusions. The chances of developing hyponatremia are increased in psychiatric patients with a seizure disorder, bipolar disorder, depression and using quetiapine or insulin. And they should be monitored carefully.